The Role of the Police in Controlling the Use of Electric Bicycles in Gorontalo City - M. Pasole; Puluhuwa, Moh. RU; Z. Mamu, Karlin (Cv. Kalimasada Group, 2025)
The widespread use of electric bicycles on the highway by the public, including children and teenagers, without complying with legal provisions has the potential for serious traffic accidents. Therefore, the role of the police in law enforcement and enforcement is important to ensure that the use of electric bicycles is in accordance with applicable regulations in the Gorontalo City area. This study aims to analyze the role of the police in handling and regulating the use of electric bicycles on the highway, especially in the Gorontalo City area, within the framework of traffic law enforcement based on Law Number 22 of 2009 concerning Traffic and Road Transportation and Regulation of the Minister of Transportation Number 45 of 2020. Electric bicycles as an alternative mode of transportation that uses battery power and electric motors are increasingly in demand by the public, including children and adolescents. However, the widespread use of electric bicycles that do not comply with legal provisions has the potential for traffic accidents, which is a serious concern for the police. This study uses an empirical legal approach by collecting data through interviews and observations of the Gorontalo City Police Traffic Unit. The results of the study show that the police have an important role in educating the public, conducting outreach, and taking firm action against traffic violations by electric bicycle users. However, limited infrastructure such as special bicycle lanes, minimal technical regulations, and lack of public legal awareness are significant obstacles in the law enforcement process. Therefore, special regulations are needed at the regional level that comprehensively regulate the use of electric bicycles, as well as collaboration between the police, local governments, and the community in building a safe, orderly, and equitable traffic system. This study recommends strengthening the supervision function and improving infrastructure as the main strategy in reducing the risk of traffic accidents due to the use of electric bicycles that do not comply with the rules.